Seroprevalence and risk factors associated with anti-Toxoplasma gondii antibodies in pregnant women attending antenatal clinics in Benue state, Nigeria - Obijiaku, Ifeoma N.; Kwaga, Jacob K.P.; Kabir, Junaidu; Lawal, Idris A.; Blake, Damer P. (International Journal of Research in Medical Sciences, 2019)
Background: Toxoplasmosis causes serious economic losses in livestock. Congenital transmission can occur in pregnant women, commonly with serious consequences. Methods: A cross-sectional study was designed to screen for the absence or presence of anti-T. gondii IgM or IgG antibodies and explore associated risk factors in pregnant women (n=261) that attended antenatal clinics in selected hospitals in Benue state, Nigeria. Blood samples were subjected to enzyme linked immunosorbent assay (ELISA). Information on sociodemographic data and possible risk factors were obtained using a structured questionnaire. Results: Out of 261 pregnant women, 19 (7.3%) and 108 (41.1%) were seropositive for anti-T. gondii IgM and IgG respectively. Comparison of IgM and IgG results suggested that 4.4% presented evidence of possible primary infection, 38.7% previous exposure, 2.8% possible reactivated or chronic infections and 51.8% were susceptible to T. gondii infection. The nature of women’s housing was significantly associated with anti-T. gondii IgM seropositivity (p <0.05). Pregnant women that lived in mud houses with thatched roofs were three times more likely to be seropositive than those who lived in concrete/brick houses with aluminium/zinc roofs (OR=3.123, 95% CI:1.027, 9.495). The study also showed that 17.7% of apparent infections were attributable to the nature of housing. More than half of the women sampled were at risk of contracting primary toxoplasmosis. Conclusion: Screening for anti- T. gondii antibodies during antenatal care is advocated in order to detect affected women so that appropriate management strategies can be implemented.